Effect of brazilian nut supplementation on antioxidant, inflammatory and lipids status in hemodialysis patients - Milena B. Stockler-Pinto; Denise Mafra; Julie C. Lobo; Cristiane Moraes; Najla E. Farage; Gilson T. Boaventura; Wellington Silva; Maria Thereza B. Wady; Olaf Malm (The Korean Society of Nephrology, 2012)
Dietary intake of selenium (Se) plays an important role as an antioxidant and anti-inflammatory agent due to its antioxidant properties and the richest known food source of Se is the Brazilian nut, found in the Amazon region, Brazil. The aim of this study was to evaluate the effect of the Brazilian nut supplementation on oxidative stress and inflammation markers and lipid stratus in HD patients. Forty HD patients (57.5% men, 53.3±16.1yrs) were studied and received 1 nut (around 5g) a day for three months. The GSH-Px, 8-isoprostane, 8-OHdG, TNF-α and IL-6 levels were determined by ELISA before and after supplementation. The LDL-c and HDL-c levels were determined by enzymatic colorimetric method using the specific kit. After 3 months supplementation, cytokines, 8-OHdG, 8-isoprostane levels decreased and the activity of GSH-Px increased significantly. Besides, after supplementation, the HDL levels increased and LDL levels decreased significantly. Parameters Before supplementation After supplementation GSH-Px (nmol/mL/min) 34.06±5.2 40.3±8.4⁎ 8-isoprostane (pg/mL) 12.2±4.5 6.6±4.6* 8-OHdG (pg/mL) 214.5(1.0−1042.0) 18.7 (1.0−78.8)* IL-6 (pg/mL) 67.1 (21.1−80.2) 13.5 (12.8−22.2)* TNF-α (pg/mL) 21.0±0.3 13.9±8.7* HDL (mg/dL) 39.0±14.2 44.7± 4.8* LDL (mg/dL) 86.0±28.7 74.7±29.5* ⁎ p<.0001 The results indicate that one Brazilian nut per day is capable to improve anti-inflammatory and antioxidant responses, and ameliorate lipids status in HD patients.